PENGARUH KETAHANAN KELUARGA TERHADAP KEGEMARAN BERMAIN GAME ONLINE PADA SISWA SD DI KELURAHAN MULYOREJO - Siti Kolipah; Shrimarti Roekmini Devy (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2016)
The family is a small unit in a nation and its existence having infl uence large enough tosuccessful the development of the power quality. Every family was expected to have the ability to exercisefunctions and its role in the economic aspect, social, psychology and culture. Changes in family haveinfl uence that is not good for families, so the family is undergoing many changes of form , function androle. The study is done to analyze relations endurance family to indulgence playing games online atprimary school student of grade IV and V Hidayatul Ummah primary school in Mulyorejo urban village,Surabaya. Research carried out to a cross sectional by adopting quantitative. Technique data collectionwas carried out by the provision of the questionnaire at 62 primary school student still was played gamesonline. The sample collection by means of simple random sampling. Variable independent to researchis family resilience (X) consisting of three variables namely variable their physic (X1), psychologicalresilience (X2) and social resilience (X3) while variable bound was a play online games (Y). The resultshowed the signifi cant infl uence of their physic family indulgence students to play online games (sig =0,000; or = 0,239). Conclusion that can be drawn is the their physic family being or good enough haveleverage large enough to play online games in children. Thus, parents must continue to monitor and limittheir children in playing online games and give education about the dangers of playing online gamesKeywords: family resilience, students, game online